Measuring the liveability of urban neighbourhoods' in Iskandar Malaysia. - Wan Azlina Wan Ismail (2019)
The notion of 'liveability' has endured for over 50 years within policy discourses, shaping urban strategy and planning across the world. This research examines the current state of liveability within the context of Iskandar Malaysia, to consider the policy rhetoric, which is created to frame urban problems, select and order concepts and build narratives that shape policy action. Liveability has a dual role: it defines normative goals for a city and also demands particular forms of expert knowledge to justify and maintain its discursive power. This duality is made meaningful when interpretations of Liveability rhetoric are implemented into liveable places. However, in this exploratory research, the interpretations of liveability are challenged by evaluating resident’s daily life experience in an urban neighbourhood in conjunction with liveability policy analysis. This research aims to address the gap in knowledge of how liveability is defined for Iskandar Malaysia’s urban neighbourhoods through critical assessment of the Comprehensive Development Plan (CDP) which is then examined in practice by measuring the degree of liveability in a number of local neighbourhoods. This research uses a variety of approaches including a theoretical discussion of the broad range of perspectives around liveability calling on critical analysis of liveability policy in Malaysia and policy guidance more widely. It also calls on opinions from professional practitioners who engage in liveability policy implementation as well as perceptions of urban residents. By exploring the experiences of residents in apparently 'liveable' neighbourhoods, differences between policy interpretations of liveability which create a representation of the neighbourhood emerge in contrast to the experience of many residents. The use of liveability dimensions and reliance on indicators generated from existing literature identified the degree of perceived liveability and everyday experience for urban neighbourhood populations in Iskandar Malaysia. This research contributes a new conceptualisation of liveability to existing knowledge which emerges from analysing together policy interpretation, experts’ insights and residents’ lived experience. This new knowledge supports existing theory, practice and policy on Liveability to some extent but refutes it elsewhere. The research recommends that to achieve policy and practice aims of providing liveable urban neighbourhoods, it is essential that the liveability of urban neighbourhoods encompasses the correlative relationship between social (communities) and spatial qualities of particular (physical) places.